Prospective study of clinical, laboratory, and ancillary staff with accidental exposures to blood or body fluids from patients infected with HIV. - McEvoy, M (1987)
In a prospective study of 150 health care workers in the United Kingdom who had been accidentally exposed to the human immunodeficiency virus no evidence of transmission was found. Larger studies in the United States and anecdotal accounts in publications from other countries confirm that the risk of occupational infection is very low. Health care workers must adopt safe procedures at all times, however, to avoid exposure to infection.